Ruthenium single‐atom modulated Ti3C2Tx MXene for efficient alkaline electrocatalytic hydrogen production - Yu Zou; Seyedeh Alieh Kazemi; Ge Shi; Junxian Liu; Yuwei Yang; Nicholas M. Bedford; Kaicai Fan; Yiming Xu; Huaiqin Fu; Mengyang Dong; Mohammad Al‐Mamun; Yu Lin Zhong; et al. (EcoMat, 2023)
Abstract Single‐atoms (SAs) supported on various substrates have emerged as a new form of electrocatalysts for hydrogen evolution reaction (HER). The exfoliated MXenes possess rich defects/vacancies and surface oxygen groups, can be favorably utilized to anchor SAs. Here, we take advantage of the exfoliated Ti3C2Tx to anchor Ru‐SAs on Ti3C2Tx through a wet‐chemistry impregnation process. The obtained RuSA@Ti3C2Tx possesses excellent HER activity, especially under high current densities. Remarkably, RuSA@Ti3C2Tx can readily attain high current densities of 1 and 1.5 A cm−2 at low over potentials of 425.7 and 464.6 mV, respectively, demonstrating its potential for practical applications. The A1g vibration frequency shift of the Raman spectrum is innovatively used to probe the surface OH coverage on Ti3C2Tx, providing critical information for mechanistic studies. The experimental and theoretical studies reveal that the superior HER electrocatalytic activity of RuSA@Ti3C2Tx results from the Ru‐SAs enhanced H2O adsorption and dissociation, and promoted H2 formation.